Avaliação participativa de variedades locais e melhoradas de milho visando a eficiência no uso de nitrogênio. - Nunes, José Arcanjo (2006)
This work was carried out to evaluate the efficiency of improved and local maize varieties considering nitrogen use in three experiments: organic cultivation; convectional cultivation using low quantity of N; and convectional cultivation using high quanti